Brave New Words: Labour, The Courts and the Canadian Charter of Rights and Freedoms - Fudge, Judy (Windsor Yearbook of Access to Justice, 2010)
In Health Services and Support – Facilities Subsector Bargaining Association v. British Columbia, [2007] 2 S.C.R. 391, the Supreme Court of Canada overturned precedent and concluded “that the grounds advanced in the earlier decisions for the exclusion of collective bargaining from the Charter’s protection of freedom of association do not withstand principled scrutiny and should be rejected” (at para. 22). The author explores the Supreme Court of Canada’s change of heart and what this change implies, not only for constitutional doctrine, but also for what the Court understands about the governance of the postFordist world of work. She situates the Court’s reasoning in a few key cases dealing with labour’s distinctive rights – to bargain collectively and to strike – in the social context that both shapes the legal discourse about labour rights and influences organized labour’s power. She considers the paradox of the Supreme Court’s embrace of Fordist labour rights in a post-Fordist economy, and suggests a modest, though important, role that the Court could play in fostering social justice in the brave new world of work.
https://www.canlii.org/w/canlii/2010CanLIIDocs28.pdf